Electrical conductivity of the Earth's mantle from the first Swarm magnetic field measurements. Issue 9 (7th May 2015) - Civet, F.; Thébault, E.; Verhoeven, O.; Langlais, B.; Saturnino, D.
Abstract We present a 1‐D electrical conductivity profile of the Earth's mantle down to 2000 km derived from L1b Swarm satellite magnetic field measurements from November 2013 to September 2014. We first derive a model for the main magnetic field, correct the data for a lithospheric field model, and additionally select the data to reduce the contributions of the ionospheric field. We then model the primary and induced magnetospheric fields for periods between 2 and 256 days and perform a Bayesian inversion to obtain the probability density function for the electrical conductivity as function of depth. The conductivity increases by 3 orders of magnitude in the 400–900 km depth range. Assuming a pyrolitic mantle composition, this profile is interpreted in terms of temperature variations leading to a temperature gradient in the lower mantle that is close to adiabatic.